Examining FLO gene expression of Saccharomyces cerevisiae in the presence of selected non-Saccharomyces strains - Brown, Mariska (Stellenbosch : Stellenbosch University, 2022)
Thesis (MScAgric)--Stellenbosch University, 2022.